Evolutionary dynamics of rRNA gene clusters in cichlid fish - Nakajima, Rafael T. [UNESP]; Cabral-de-Mello, Diogo Cavalcanti [UNESP]; Valente, Guilherme T. [UNESP]; Venere, Paulo C.; Martins, Cesar [UNESP] (Biomed Central Ltd., 2012)
Background: Among multigene families, ribosomal RNA (rRNA) genes are the most frequently studied and have been explored as cytogenetic markers to study the evolutionary history of karyotypes among animals and plants. In this report, we applied cytogenetic and genomic methods to investigate the organization of rRNA genes among cichlid fishes. Cichlids are a group of fishes that are of increasing scientific interest due to their rapid and convergent adaptive radiation, which has led to extensive ecological diversity.Results: The present paper reports the cytogenetic mapping of the 5S rRNA genes from 18 South American, 22 African and one Asian species and the 18S rRNA genes from 3 African species. The data obtained were comparatively analyzed with previously published information related to the mapping of rRNA genes in cichlids. The number of 5S rRNA clusters per diploid genome ranged from 2 to 15, with the most common pattern being the presence of 2 chromosomes bearing a 5S rDNA cluster. Regarding 18S rDNA mapping, the number of sites ranged from 2 to 6, with the most common pattern being the presence of 2 sites per diploid genome. Furthermore, searching the Oreochromis niloticus genome database led to the identification of a total of 59 copies of 5S rRNA and 38 copies of 18S rRNA genes that were distributed in several genomic scaffolds. The rRNA genes were frequently flanked by transposable elements (TEs) and spread throughout the genome, complementing the FISH analysis that detect only clustered copies of rRNA genes.Conclusions: The organization of rRNA gene clusters seems to reflect their intense and particular evolutionary pathway and not the evolutionary history of the associated taxa. The possible role of TEs as one source of rRNA gene movement, that could generates the spreading of ribosomal clusters/copies, is discussed. The present paper reinforces the notion that the integration of cytogenetic data and genomic analysis provides a more complete picture for understanding the organization of repeated sequences in the genome.